Synergistic therapeutic strategies for metabolic dysfunction-associated steatohepatitis and type 2 diabetes mellitus: molecular insights and clinical advances - Zhu, Bo (Frontiers in Endocrinology, 2026)
Metabolic dysfunction-associated steatohepatitis (MASH) and type 2 diabetes mellitus (T2DM) are closely linked conditions that share common disturbances in metabolism, inflammation, and fibrotic processes. MASH is characterized by fat accumulation in the liver, hepatocyte damage, and progressive fibrosis, whereas T2DM involves insulin resistance and impaired beta-cell function. The coexistence of these disorders creates a liver and pancreas feedback loop, in which impaired hepatic insulin signaling worsens blood glucose control and high glucose levels further damage the liver. Key cellular contributors include hepatocytes, Kupffer cells, hepatic stellate cells, and pancreatic β-cells, while non-coding RNAs influence lipid metabolism and inflammation. Emerging therapies, including GLP1 receptor agonists, dual incretin agents, PPAR modulators, thyroid hormone receptor beta modulators, FXR agonists, and FGF analogues, along with lifestyle interventions, show promise in improving both liver and metabolic outcomes. Precision medicine approaches may further refine individualized treatment strategies.